KONTRIBUSI MODAL DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG DI PASAR UMUM PEKUTATAN, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA - Pariartha, I Wayan Wana (PIRAMIDA; Vol 3, No.2 Desember 2007)
Income is very essential to merchants in a public market and it is closely related to how much their products are in demand. A high demand, reflected from the hustle and bustle of a market, will automatically raise to merchants, income and vice versa. The merchants in a public market generally run their business on a small-scale capital and therefore its turnover is very fast so as to make the capital very productive. Their capital turnover is very much influenced by such factors as the size of the capital, manpower, working hours, experience, and so forth. This research took place at Pekutatan Public Market, District of Jembrana. There were 36 respondents which were randomly selected out of 120 merchant. The data was collected through interviews based on a set of predetermined quistions as a reference. The average capital which is spent by the merchants at the Pekutatan Public Market is Rp. 1.351.070,00 with an average working hours of 48.76 hours per week. Their income is Rp. 1.325.758,82 per week. As a whole, the amount of capital and working hours have an immdiate impact on the income with a degree of freedom up to 1%. However, those factors respectively contribute in part to the degree of freedom up to 5%. The capital has the trongest influence, followed by the working hours. This can be concluded that the capital serves as the most dominant factor in determining the income.
Keywords: puplic market, merchant, capital, income, working hours.